Normobaric Oxygen May Ameliorate Cerebral Venous Outflow Disturbance-Related Neurological Symptoms - Ding, Jiayue; Liu, Yu; Li, Xiangyu; Chen, Zhiying; Guan, Jingwei; Jin, Kexin; Wang, Zhongao; Ding, Yuchuan; Ji, Xunming; Meng, Ran (Frontiers in Neurology, 2020)
Cerebral venous outflow disturbance (CVOD) has begun to garner the attention of researches owing to a series of clinical symptoms that impose a significant impact on people's quality of life. Herein, we aimed to investigate whether normobaric oxygen (NBO) can ameliorate CVOD-induced neurological symptoms. This was one part of the prospective trial registered in ClinicalTrials.gov (NCT03373292). A total of 37 CVOD patients were divided into the NBO group (5–8 L/min of oxygen inhalation, 1 h per time, 3 times daily, n = 19) and the control group (without oxygen inhalation, n = 18) randomly. The assessments were performed at admission, 1-week hospitalization, and 6-month follow-up. Quantitative electroencephalogram (qEEG) data were recorded prior to and post 1 h of NBO in some patients. R software was used for data analysis. No NBO-related adverse events were observed during the whole NBO intervention process. The 1-week Patient Global Impression of Change (PGIC) scale showed that the symptom improvement occurred in nine patients in the NBO group (47.4%) while none in the control group (p = 0.001). NBO could improve headache evaluated with visual analog scale (pre-NBO vs. post-NBO: 4.70 ± 2.16 vs. 2.90 ± 2.03, p = 0.024) and Headache Impact Test-6 (53.40 ± 12.15 vs. 50.30 ± 13.04, p = 0.041). As for 6-month PGIC follow-up, eight out of 14 cases (57.1%) in the NBO group reported improvement, while only one out of 12 patients in the control group replied mild improvement (p = 0.014). The qEEG revealed that NBO reduced the ratio of theta to alpha power (0.65 ± 0.38 vs. 0.56 ± 0.35, p = 0.030) over the fronto-central electrodes. To sum up, NBO may be a safe and effective approach to attenuate CVOD-related symptoms (especially for headache) by brain functional improvement resulting from increasing oxygen supply to the brain tissues.